Osteogenic and Neurogenic Stem Cells in Their Own Place: Unraveling Differences and Similarities Between Niches - Lattanzi, Wanda; Parolisi, Roberta; Barba, Marta; Bonfanti, Luca (Frontiers in Cellular Neuroscience, 2015)
Although therapeutic use of stem cells is already available in some tissues (cornea, blood, skin), in most organs we are far from reaching the translational goal of regenerative medicine. In the nervous system, due to intrinsic features which make it refractory to regeneration/repair,it is very hard to obtainfunctionally-integrated regenerative outcomes, evenstarting from its own stem cells(the neural stem cells; NSCs). Besides NSCs, mesenchymal stem cells (MSCs) have also been proposed for therapeutic purposes in neurological diseases. Yet, direct (regenerative) and indirect (bystander) effects are often confused, as are MSCs and bone marrow-derived (stromal, osteogenic) stem cells (BMSCs), whoseplasticity isactually overestimated (i.e. trans-differentiation along non-mesodermal lineages, including neural fates).In order to better understand failure in the "regenerative" use of stem cells for neurological disorders,it could be helpful to understand how NSCs and BMSCs have adapted to their respective organ niches. In this perspective, here the adult osteogenic and neurogenic niches are considered and compared within their in vivo environment.